Care burden and quality of life among family caregivers of children with cerebral palsy in China: the mediating roles of social support and coping styles - Fang Liu; Rui Zhang; Cui Cui; Hengyu Zhou (BMC Public Health)
Abstract Background Children with cerebral palsy have substantial caregiving demands, and the overall health of their caregivers is greatly affected. The contributing variables to caregivers’ quality of life must be identified. Our attention will be paid to the impact of caregiver’s social resources such as social support and caregiver’s personal resources such as coping styles on their care situation. Aims To explore the relationships among care burden, social support, coping styles, and QOL of caregivers for cerebral palsy children by mediation effect models. Design A cross-sectional study design. Methods The purposive sampling method was used in this study to select 189 caregivers of cerebral palsy children from the rehabilitation department of a children’s hospital in western China from May 2022 to August 2023. Self-designed demographic data questionnaire, the WHO’s Quality of Life Questionnaire, the Zarit Burden Interview, the Social Support Rating Scale, and the Simplified Coping Style Questionnaire were used for conducting the investigation. Correlations analyses between variables were analyzed using Pearson’s correlation coefficient. The mediating effects were explored using the Process Macro and bootstrap method. Results Among the 189 caregivers, 59.26% were mothers, 64.55% had received high school or lower education. The majority of caregivers were not employed (62.96%). Care burden had a detrimental impact on both physical QOL and mental QOL. Social support and positive coping style were positively correlated with physical and mental QOL. Among the mediation analyses, significant indirect effects were found for the mediation path of social support between care burden and either physical or mental QOL. Whereas positive coping style as a mediator was not statistically significant. Additionally, social support and positive coping style formed a significant serial mediation path. Conclusion Caregivers of cerebral palsy children suffer from a certain level of caregiving burden and an unsatisfactory living quality. Social support alone or in combination with positive coping style played mediating roles in connection of care burden and QOL. Future interventional research ought to prioritize boosting social support and developing positive coping style since they may exert the synergistic effect on both physical and mental QOL of caregivers.